Imaji “Virtual library ” Jendela Perpustakaan - Nasrul Rizal A. Lubis (Jurnal Pari, 2017)
ABSTRAKPerpustakaan maya atau perpustakan digital memegang peranan penting dalam mempromosikan penggunaaninformasi. Perpustakaan digital memberikan solusi untuk tantangan utama perpustakaan tradisional seperti penyimpanan.Makalah ini membahas konsep perpustakaan digital dan bagaimana hal ini membantu dalam melestarikan manuskrip danjenis peralatan atau perangkat lunak apa yang dibutuhkan dalam pekerjaan ini. Informasi digital di setiap bidang sehinggasetiap perpustakaan harus menjadi perpustakaan digital.ABSTRACTThe virtual library or digital library plays an important role in promoting the use of information. Digital libraries givesolutions to main challenges to traditional libraries such as storage. This paper discusses the concept of digital libraryand how it helps in conserving manuscripts and what type of equipments or software are required in this work. Digitalinformation in every field so that every library should be a digital library.